2001
DOI: 10.1103/physrevlett.86.1251
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous High Pressure Dependence of the Jahn-Teller Phonon inLa0.75Ca0.25MnO3

Abstract: Raman spectra of La(0.75)Ca(0.25)MnO(3) have been collected for the first time over a wide pressure range (0-14 GPa) using a diamond anvil cell. The frequency range explored (200-1100 cm(-1)) and the very good quality of the data allowed us to carefully analyze the pressure evolution of the phonon modes of the MnO(6) octahedra. The results show an abrupt transition at approximately 7.5 GPa with an evident deviation from the linear trend of the frequency of the Jahn-Teller phonon versus the applied pressure, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
85
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 24 publications
16
85
0
Order By: Relevance
“…Since the Raman spectrum of VO 2 in the R phase is characterized by only 4 broad peaks [29,30] we can safely conclude at a glance that a transition to a R phase is not achieved by applying pressure up to 19 GPa. The good quality of the data allows to apply a standard fitting procedure [20] to analyse the pressure dependence of the phonon spectrum. The analysis shows an almost linear increase of the frequencies of every phonon peak eccept for ω V 1 and ω V 2 at 192 cm −1 and 224 cm −1 at P∼0, respectively, whose pressure dependence is shown in the inset of Fig.…”
Section: Pacs Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the Raman spectrum of VO 2 in the R phase is characterized by only 4 broad peaks [29,30] we can safely conclude at a glance that a transition to a R phase is not achieved by applying pressure up to 19 GPa. The good quality of the data allows to apply a standard fitting procedure [20] to analyse the pressure dependence of the phonon spectrum. The analysis shows an almost linear increase of the frequencies of every phonon peak eccept for ω V 1 and ω V 2 at 192 cm −1 and 224 cm −1 at P∼0, respectively, whose pressure dependence is shown in the inset of Fig.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…The gaskets were made of a 250 µm thick steel foil with a sample chamber of 130 µm diameter and 40 to 50 µm height under working conditions. We used NaCl an KBr as pressure transmitting media for Raman and MIR measurements respectively [20,21]. Pressure was measured in situ with the standard ruby fluorescence technique [22].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…But we argue that this is a very clear evidence that the feature up there is second order phonon scattering. In fact, the HFC structure is also present in Sr doped manganites, and all other pseudocubic and double layer manganites [22,23] and we believe that such features are weak second-order Raman scattering effects (density of state), mirroring the bands seen in the region 400-800 cm −1 . The frequencies of the experimental peaks are plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Note that a high frequency oscillator (near 1100 cm −1 ) is necessary to achieve a good fit. It should be pointed out that this High Frequency Contribution (HFC) is also found in Raman experiments on La 0.75 Ca 0.25 MnO 3 [22], and it has been suggested that the HFC should be associated with the photoionization of small polarons. But we argue that this is a very clear evidence that the feature up there is second order phonon scattering.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectroscopy is an ideal and relatively straightforward technique to test quantum confinement. Moreover, it can be realized under many extreme and non-extreme conditions, leading to an ideal technique for the investigation of processes in matter at low/high temperatures and/or high pressures (Iwasa et al, 2004;Kim et al, 1996;Wright et al, 1997;Weinstein et al, 1975;Congeduti et al, 2001). Indeed, phonon scattering in crystals of small dimension leads to a redshift and broadening of the first order Raman line.…”
Section: Phonon Quantum Confinement In Nanowiresmentioning
confidence: 99%